A Survey On Marine Fish Species In River of Mahakam East Kalimantan, Indonesia - Iwan Suyatna; Muhammad Syahrir; Mislan Mislan; Yuni Irawati Wijaya; Abdunnur Abdunnur (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
A first survey on a community marine species in river of Mahakam East Kalimantan was performed in December 2015 and May 2016. Fish samplings were carried out from two locations the lower and the middle part of Mahakam. Whilst hydrometric observation of current velocity, water depth and tide was measured not only at the locations but also along the river from 2013 to 2017, tide was only observed in the lower part of Mahakam. However, marine fish species were recognized to reach up the middle part of Mahakam, 230 km from coastline. To describe a community fish structure and its dissimilarity of the two surveyed locations, diversity and bray Curtis index were applied. Almost 15 marine fish species identified in river of Mahakam was demersal fish and index of the similarity of marine fish community between the locations only 0.106.